Evaluation of Cortical Brain Parenchyma by Diffusion and Perfusion MRI Before and After Chronic Subdural Hematoma Surgery - Akgun, Bekir; Cakin, Hakan; Ozturk, Sait; Yildirim, Hanefi; Okcesiz, Izzet; Kazan, Saim; Erol, Fatih Serhat (Turkish Neurosurgical Soc, 2018)
AIM: To evaluate microcirculatory changes in neighboring parenchyma as a result of pressure due to chronic subdural hematoma (CSDH) in early and late periods after hematoma drainage. MATERIAL and METHODS: The subject group consisted of 25 patients who underwent CSDH drainage. Brain diffusion and perfusion magnetic resonance images (MRIs) were obtained preoperatively, and at 48 hours (early period) and 2 months (late period) postoperatively. Measurements were performed on 1 cm(2) regions of interest (ROI) in the neighboring parenchymal tissue. RESULTS: The early postoperative diffusion values showed improvement compared to the preoperative values. The late postoperative values showed improvement compared to the preoperative and early postoperative values. The early postoperative perfusion values showed slight decline compared to the preoperative values. However, the late postoperative values showed improvement compared to the preoperative and early postoperative values. CONCLUSION: The fact that there was an increase in diffusion values from early to late postoperative periods, compared with the preoperative period, indicates that the beneficial effects of surgery increase over time. Brain perfusion was found to be slightly decreased in early postoperative period. Following CSDH drainage, neurological deteriorations are observed in some patients in the early postoperative periods; a slight impairment in perfusion may account for this. However, during the late postoperative period, perfusion was seen to recover prominently.
Keywords: Chronic subdural hematoma; Diffusion; Perfusion; Magnetic resonance imaging